Evaluation of fungicides and bioagents for the control of charcoal rot of sesame caused by Macrophomina phaseolina - Saurabh, Kumar; Saharan, H S; Rathi, A S; Kumar, Mukesh (Indian Journal of Plant Protection, 2020)
Experiments on efficacy of fungicides and bioagents were tested in vitro for the per cent mycelial growth inhibition and in vivo for the control of charcoal rot caused by Macrophomina phaseolina at CCS HAU, Hisar during Kharif 2016. Thiram + carboxin, carboxin and thiram alone completely inhibited mycelial growth up to 100 per cent at 400 ppm concentration followed by carbendazim, tebuconazole and captan having mycelial growth inhibition of 97.1, 91.8 and 82.3 per cent, respectively at higher concentration of 1000 ppm. Three bioagents, viz.,Trichoderma viride, T. harzianum and Pseudomonas fluorescens were tested for the inhibition of mycelial growth of M. phaseolina in vitro. T. viride inhibited the mycelial growth up to 71.2 per cent followed by T. harzianum (63.6%),while the bacterial bioagent P. fluorescens could only inhibit 37.8 per cent of mycelial growth. Two best fungicides as seed treatment and two bioagents as soil inoculants were tested for their efficacy under screen house conditions.Maximum disease control was achieved by seed treatment with thiram + carboxin @ 2 g/kg seed, which controlled the disease up to 77.2 per cent followed by thiram @ 2 g/kg seed which controlled the disease up to 69.0 per cent.While, among the bioagents, T. viride showed significantly higher disease control of 54.4 per cent followed by T. harzianum, which controlled the disease up to 40.9 per cent.